Case study of occupational mercury exposure during decontamination of turnaround in refinery plant. (2nd January 2017) - Muadchim, Maytiya; Phanprasit, Wantanee; Robson, Mark Gregory; Sujirarat, Dusit; Detchaipitak, Rawee
Abstract: Decontamination during turnaround (TA) can lead to high exposure to toxic chemicals among workers. The decontamination process in refinery plants usually comprises two types, i.e. steam and chemical decontamination. No matter the method used, concentrations of toxic chemicals must be measured using the direct reading instrument at the end of each decontamination cycle, which maybe repeated several times until the readings are in acceptable level. To evaluate mercury exposure of decontamination workers during decontamination procedure in comprehensive turnaround of a refinery plant. Thirty personal and 16 area air samples were collected using passive dosimeters and absorbent tubes, respectively, during 8 days of the decontamination in comprehensive turnaround. All samples were analyzed using inductively coupled plasma mass spectrometry (ICP-MS). Good practices and standard procedures for air sampling and analysis were performed. The TWA concentrations were calculated and compared between steam and chemical decontamination workers. All area samples were well below TLV (ND – 0.0016 mg/m 3 ) while 5 of 14 samples collected at the steam team and 1 of 16 samples taken from the chemical team exceeded the TLV. The geometric mean (GSD) of TWA concentration of the steam team was 0.0057(10.4906) mg/m 3, which is about twice as high as that of the chemical team, 0.0031(6.9422) mg/m 3 . The highest mercury concentration, 0.1037 mg/m 3, was collected from a steam decontamination worker. According to the activities and observation, the steam team may have high exposure while reading the chemical concentrations at the end of the decontamination cycle.